“What we write is used against us”: The participants’ views on tightened control in online debate after the Oslo terrorist attacks - Ihlebæk, Karoline Andrea; Løvlie, Anders Sundnes (AoIR Selected Papers of Internet Research, 2013)
This paper investigates the participants’ experience of changes in the editorial control with online debate after the 22 July 2011 terrorist attacks in Norway. Through a large-scale web survey and in-depth interviews with a small group of respondents it is uncovered that a majority of the respondents experience a tightening of editorial control, and a reduction in their freedom to participate in the debate. The participants express suspicion and a lack of understanding of the moderation policies of the newspapers, indicating a need for the media organisations to improve the transparency of moderating practices towards participants. Furthermore, participants express a strong preference for being able to comment anonymously, and fear of potential repercussions if being forced to use their real names when commenting, indicating that taking away the possibility to be anonymous may curb participation in online debate.